ANALISIS HUBUNGAN AKTIVITAS KENDARAAN BERMOTOR TERHADAP KONSENTRASI SO2 DAN NO2 DI UDARA AMBIEN (STUDI KASUS: JL. PANEMBAHAN SENOPATI YOGYAKARTA) - Sri Hastutiningrum; Sri Sunarsih; Imelda - (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2018)
The aims of this study is to determine the correlation between vehicle traffic activity and the effect of sampling time on the SO2 and NO2 concentration in ambient air. The sampling location is on Jl. Senopati Yogyakarta. Sampling was carried out by an air absorbtion tool with 1.5-meter-high auxiliary from the ground. To measure SO2 using Pararosanilin method and Griess Saltzman method for NO2. The stages of this study begin with the preparation of TCM absorption solutions for SO2, Griess Saltzman absorbent solution for NO2, calibration curve manufacture, and vehicle volume calculation. Determination of concentration is done by UV-Vis spectrophotometer Thermo Scientific Genesys 20. Time sampling is divided into weekdays (Tuesday-Wednesday) and weekend (Saturday-Sunday) with sampling time on 03.00-04.00, 07.00-08.00 a.m, and 12.00-01.00, 04.00-05:00 and 07.00-08.00 p.m. The result of the study shows that the concentration of SO2 and NO2 in ambient air is not related (correlated) with vehicle activity at Jl. Senopati Yogyakarta,as well as sampling time that did not affected. The highest SO2 concentration was recorded at 232,05μg/Nm3 while the highest NO2 concentration was 17.9522 μg/Nm3. Both is not exceed of air quality standard 900μg/Nm3 and 400 μg/Nm3.